Organic Fertilizers as Partial Substitutes for Chemical Fertilizers Enhance Nitrogen Immobilization and Optimize Nitrogen Fate in Paddy Soils - Hongqian Hou; Jianhua Ji; Xianjin Lan; Marios Drosos; Xiumei Liu; Zhenzhen Lv; Yiren Liu; Zhengxin Cheng; Weijun Zhou (Agriculture)
Organic fertilizers as partial substitutes for chemical fertilizers improve soil nitrogen (N) retention capacity. However, the relative importance of biotic and abiotic N immobilization at different levels of organic N substitution and the subsequent effects on N utilization in paddy soils are not well elucidated. To address these, a combination of 15N incubation experiments and pot experiments were conducted to investigate biotic and abiotic N immobilization features and their effects on N fertilizer fate under long-term different fertilization regimes in paddy soils in China. Test soils that had received chemical fertilization (NPK), chemical N was substituted with 30%, 50%, and 70% organic N (70 F + 30 M, 50 F + 50 M, and 30 F + 70 M, respectively), and no fertilization (control) for 36 years. The results revealed that both abiotic and biotic NH4+-N immobilization were enhanced under organic N substitution soils. The highest NH4+-N abiotic and biotic N immobilization was observed under 50 F + 50 M soil, significantly increasing by 195.5% and 51.4%, respectively, compared to the NPK soil. In contrast, only abiotic NO3−-N immobilization increased with rising organic substitution N proportions. N fertilizer utilization efficiency was significantly enhanced in 50 F + 50 M soil (36.7%) compared to the NPK soil (30.3%), which was primarily attributed to the enhanced N pool activity and N immobilization capacity. However, the N fertilizer residue rate was significantly higher in the 30 F + 70 M soil (23.6%) compared to the NPK soil (21.6%), largely attributed to the soil properties improvement. Our results suggest that N immobilization capacity and N fertilizer utilization can be optimized with a 50% organic substitution ratio in our studied soil–crop system.